Foreign language teachers and intercultural competence : an international investigation - Sercu, Lies (Languages for intercultural communication and education, 2005)
This volume reports on a study that focused on teachers' beliefs regarding intercultural competence teaching in foreign language education. Its conclusions are based on data received from teachers in seven countries: Belgium, Bulgaria, Poland, Mexico, Greece, Spain and Sweden.